The effect of movement variability on putting proficiency during the golf putting stroke - Richardson, A. K.; Mitchell, A. C. S.; Hughes, G. (International Journal of Sports Science & Coaching, 2018)
Movement variability has been considered important to execute an effective golf swing yet is comparatively unexplored regarding the golf putt. Movement variability could potentially be important considering the small margins of error between a successful and a missed putt. The aim of this study was to assess whether variability of body segment rotations influence putting performance (ball kinematic measures). Eight golfers (handicap range 0-10) performed a 3.2m level putt wearing retro-reflective markers which were tracked using a three-dimensional motion analysis system sampling at 120Hz. Ball roll kinematics were recorded using Quintic Ball Roll launch monitor. Movement (segment) variability was calculated based on a scalene ellipsoid volume concept and correlated with the coefficient of variation of ball kinematics. Statistical analysis showed no significant relationships between segment variability and putting proficiency. One significant relationship was identified between left forearm variability and horizontal launch angle, but this did not result in deficits in putting success. Results show that performance variability in the backswing and downswing is not related to putting proficiency or the majority of ball roll measures. Differing strategies may exist where certain golfers may have more fluid movement patterns thereby effectively utilising variability of movement. Therefore, golf instructors should consider movement variability when coaching the golf putt.